Clear cell papillary renal cell carcinoma is an indolent and low‐grade neoplasm with overexpression of cyclin‐D1. Issue 7 (20th February 2014) - Leroy, Xavier; Camparo, Philippe; Gnemmi, Viviane; Aubert, Sebastien; Flamand, Vincent; Roupret, Morgan; Fantoni, Jean‐Christophe; Comperat, Eva
<x xml:space="preserve">Abstract</x> Aims Several entities have been individualized recently within the family of renal neoplasms with papillary features. Clear cell papillary renal cell carcinoma (CCPRCC) was first described in patients with end‐stage renal disease, but is also observed in patients with normal renal function. The objective of this study was to document the clinicopathological and immunohistochemical characteristics of CCPRCC, with a special emphasis on cyclin D1 expression. Methods and results The patients were 25 men and 17 women, mean age 60.7 years. Seventeen patients had a chronic renal disease. All tumours were stage pT1, with a mean diameter of 2 cm. Six tumours were multifocal. Tumours cells were mainly cuboidal, with clear cytoplasm and low‐grade nuclei apically aligned. In all cases, Fuhrman nuclear grade was one or two. No necrosis or vascular invasion was seen. During follow‐up (10–72 months), no metastasis or death related to the disease was observed. Immunohistochemistry showed strong and diffuse cytokeratin 7 immunoreactivity in all cases, but no labelling for AMACR or TFE3. There was diffuse nuclear cyclin D1 immunoreactivity in 83% of cases. Conclusion CCPRCC is now a well‐characterized entity. This tumour is an indolent and very low‐grade neoplasm. Here we report the first study, to our knowledge, demonstrating the overexpression of cyclin D1 immunostaining by this tumour.